Nigerian Agricultural Posts on Facebook and Instagram within the West African Agricultural Messaging Framework - Aliagan, Isiaka Zubair; Ahmad, Murtada Busair; Daranijo, Habeeb Opeyemi; Na’allah, Habibat Bolajoko (Universitas Muhammadiyah Yogyakarta, 2023)
This study generated and content-analyzed Facebook and Instagram postings on agricultural messages by Nigerian farmers in three years (2019-2021) within specific contexts and in comparison with postings similar to ones initiated by private individuals and government agencies as well as those posted at continental level on the two social media channels. While the data are graphically displayed, a paired-sample T-test was conducted to establish statistically significant differences in the agricultural messages posted on the two social media by Nigerian farmers and farmers from other countries in Africa. All four null hypotheses tested were rejected as statistically significant differences were established between the paired population means. It was also found that Nigerian farmers are accustomed to the use of social media in promoting agricultural-related messages, indicating their exposure to the diffusion of agricultural innovation in line with the trends in advanced nations. It was concluded that social media remains a viable tool for promoting agriculture, particularly during food insecurity and global economic crisis. It was recommended that the Nigerian government should provide an enabling environment for agricultural promotion in the digital age.